Analysis of Local Media Content on the Implementation of Air Pollution Control Policies - Bunga Astini; Yasir Yasir; Eko Hero (Universitas Lambung Mangkurat, 2025)
Air pollution in Riau Province is an environmental problem that has been going on for years, with significant impacts on public health, the environment, and the economy. One of the main causes of air pollution is forest and land fires (karhutla), which are generally caused by land clearing practices for agriculture and oil palm plantations. Although various efforts have been made to overcome air pollution, its implementation in Riau Province still faces a number of challenges, such as lack of socialization, suboptimal supervision, and weak law enforcement against perpetrators of arson. This study aims to examine how air pollution control policies are implemented in Riau Province through analysis of local media coverage from 2021 to 2024. The method used is qualitative research with a descriptive approach, which focuses on analyzing news content related to air pollution control policies. The results of the study show that although various policies have been implemented, challenges in supervision and public awareness still hinder the effectiveness of air pollution control efforts. This study provides recommendations for policy makers to strengthen coordination between agencies, increase public education, and improve supervision for more effective air pollution reduction in the future.